Spoligotyping of Clinical Isolates of Mycobacterium tuberculosis Complex Species in the Oromia Region of Ethiopia - Hussien, Bedru; Zewude, Aboma; Wondale, Biniam; Hailu, Awraris; Ameni, Gobena (Frontiers in Public Health, 2022)
Abstract Background: Tuberculosis (TB) is the leading cause of morbidity and mortality in Ethiopia. Investigation of the Mycobacterium tuberculosis complex (MTBC) species circulating in the Ethiopian population would contribute to the efforts made to control TB in the country. Therefore, this study was conducted to investigate the MTBC species and spoligo patterns in the Oromia Region (central) of Ethiopia. Methods: A cross-sectional study design was used to recruit 450 smear positive pulmonary TB cases from the Oromia Region between September, 2017 and August, 2018. Mycobacteria were isolated from sputum samples on the Lowenstein Jensen (LJ) medium. Molecular identification of the isolates was performed by spoligotyping. The results of spoligotyping were transferred into query box in the SITVIT2 database and Run TB-Lineage in the TB Insight website for the identification of spoligo international type (SIT) number and linages of the isolates, respectively. Statistical Product and Service Solutions (SPSS) 20 was applied for statistical analysis. Results: Three hundred fifteen isolates were grouped under 181 different spoligotype patterns. The most dominantly isolated spoligotype pattern was SIT149 and it consisted of 23 isolates. Majority of the isolates were grouped under Euro-American (EA), East-African-Indian (EAI), Indo-Oceanic (IO) lineages. These lineages consisted of 79.4%, 9.8%, 9.8% of the isolates, respectively. One hundred sixty-five of the isolates were classified under 31 clustered spoligotypes while the remaining 150 were singleton types. Furthermore, 91.1% of the total isolates were classified as orphan types. Clustering of spoligotypes was associated (p<0.001) with EAI Lineage. Conclusion: SIT149 and EA Lineage were predominantly isolated from the Oromia Region substantiating the findings of the similar studies conducted in other regions of Ethiopia. The observation of significant number of singleton and orphan spoligotypes warrants for additional genetic typing of the isolates using method(s) with a better discriminatory power than spoligotyping.